A new species of Acanthosaura Gray 1831 (Reptilia: Agamidae) from central Vietnam - Nguyen, Sang Ngoc; Jin, Jie-Qiong; Vo, Ba Dinh; Nguyen, Luan Thanh; Zhou, Wei-Wei; Che, Jing; Murphy, Robert W.; Zhang, Ya-Ping (Zootaxa, 2019)
Herein, we describe the new agamid species Acanthosaura phongdienensis sp. nov. from central Vietnam based on morphological and genetic data. Males of the new medium-sized species have a snout-vent length of up to 77.4 mm and females up to 64.7 mm. In both genders, the tail is longer than the snout-vent length. A spine occurs on each side of the neck, the rostral scute is entire, and the nuchal and dorsal crests are continuous. A postorbital spine is about half as long as the diameter of the eye-ball, and small lateral scales intermix with large, keeled scales whose tips point backwards and upwards. The new species differs genetically from the closely related species A. brachypoda, A. coronata, and A. lepidogaster by uncorrected p-distances of 13.6%, 21.7%, and 12.8%, respectively. This is the 13th species of Acanthosaura and the eighth species in the genus from Vietnam.